An Assistive Technology Framework for SDGs-Based Educational Games for Elementary School Children with Physical Disabilities - Muhammad Perwiranegara; Melyani Handoko; Miranti Handayani; Windu Tiastuti; Faif Yusuf; Suci Riyanti (University of Science and Computer Technology, 2026)
The Sustainable Development Goals (SDGs) emphasize inclusive and equitable quality education for all learners. However, children with physical disabilities frequently encounter barriers when accessing digital educational resources, particularly educational games that lack accessibility features. This study proposes a Framework of Assistive Tools integrated into SDGs-based educational games to improve learning accessibility and achievement among elementary school children with physical disabilities. The framework consists of four interconnected layers: SDGs Layer, Educational Game Layer, Accessibility Layer, and Assistive Tools Layer. A quasi-experimental approach involving 30 elementary school students with physical disabilities was employed to evaluate the framework. Learning achievement, accessibility, engagement, and usability were assessed through pre-test and post-test evaluations. Simulated results indicate a significant increase in learning achievement from 63.4 to 77.5, representing a 22.2% improvement. Structural Equation Modeling using Partial Least Squares (PLS-SEM) demonstrated positive relationships among assistive tools, accessibility, educational game effectiveness, and learning achievement. The findings suggest that integrating assistive technologies into educational games contributes significantly to SDG 4 (Quality Education) and SDG 10 (Reduced Inequalities). The proposed framework can serve as a guideline for future development of inclusive educational technologies.